Factors Affecting Loneliness in Overseas Students: A Scooping Review - Arif Putra Basir; Nur Setiawati Dewi; Megah Andriany (GLOBAL HEALTH SCIENCE GROUP, 2025)
Overseas students have a high risk of experiencing loneliness due to increased social demands and feelings of homesickness. There have been many studies on factors affecting loneliness in overseas students, but there has been no explanation that discusses cultural factors, social isolation, social support, discrimination, geography and adaptation. Objective: This study was conducted to explore research findings related to factors that influence loneliness in overseas students. Methods: Researchers used the scoping review method to get a clear picture of the factors that influence loneliness in overseas students. A literature search was conducted using the keywords “loneliness factor” AND “overseas” AND “students”. The databases used were Sciencedirect, Scopus, and Pubmed. Inclusion criteria were articles from publications in the last 5 years (2019-2023), articles in English, quantitative and qualitative research with the research population in the form of loneliness in overseas students, the article was accessible. Screening was stepwise and documented according to the PRISMA flowchart. Results: Based on identification, there were 224 articles from sciencedirect, scopus, and pubmed. 9 articles were obtained that fit the criteria after going through the selection process. Researchers used the PEO question format (population, exposure, results) to find related research articles. Conclusion: Based on the analysis of 9 literatures, it is concluded that loneliness in overseas students is influenced by many factors such as cultural factors, social support, discrimination, geography, and adaptation.